NeuroMorph: A Software Toolset for 3D Analysis of Neurite Morphology and Connectivity - Jorstad, Anne; Blanc, Jérôme; Knott, Graham (Frontiers in Neuroanatomy, 2018)
The geometries of axons, dendrites and their synaptic connections provide important information about their functional properties. These can be collected directly from measurements made on serial electron microscopy images. However, manual and automated segmentation methods can also yield large and accurate models of neuronal architecture from which morphometric data can be gathered in 3D space. This technical paper presents a series of software tools, operating in the Blender open source software, for the quantitative analysis of axons and their synaptic connections. These allow the user to annotate serial EM images to generate models of different cellular structures or to make measurements of models generated in other software. The paper explains how the tools can measure the cross-sectional surface area at regular intervals along the length of an axon, and the amount of contact with other cellular elements in the surrounding neuropil, as well as the density of organelles, such as vesicles and mitochondria, that it contains. Nearest distance measurements, in 3D space, can also be made between any features. This provides many capabilities such as the detection of boutons and the evaluation of different vesicle pool sizes, allowing users to comprehensively describe many aspects of axonal morphology and connectivity.